2015
DOI: 10.1177/0265659015569549
|View full text |Cite
|
Sign up to set email alerts
|

Exploring parental perspectives of participation in children with Down Syndrome

Abstract: The everyday lives of children with disabilities are not well understood, with few studies exploring how participation in everyday life is conceptualized and given meaning. The overall aims of this study were, first, to explore parental views of their children’s participation and, second, to identify barriers and facilitators in relation to participation in everyday activities. A qualitative research strategy was adopted, whereby parents of children with Down syndrome (DS) aged 6–12 years were selected using p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0
20

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(71 citation statements)
references
References 48 publications
3
48
0
20
Order By: Relevance
“…Twenty-three studies indicated that the data came from parents or caregivers [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Authors of 16 studies reported that the mother was the sole respondent for all data [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-three studies indicated that the data came from parents or caregivers [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Authors of 16 studies reported that the mother was the sole respondent for all data [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Family Demands and Children’s Social Participation. Lyons et al [ 42 ] explored which barriers influenced activities and participation in everyday activities among children with DS (social inclusion). Choi and Yoo [ 33 ] examined how parental depression and family strain were related to stigma/discrimination experiences of children with DS (rights).…”
Section: Resultsmentioning
confidence: 99%
“…Outdoor play affords children opportunities to develop independence, self‐determination and physical skills (Stephenson, ), and foster a sense of wellbeing and belonging (Bundy et al, ; Lyons, Brennan, & Carroll, ). The inclusion of loose materials, opportunities for risk and unstructured time can increase the inclusivity of play (Barbour, ; Bundy et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, inclusion is a complex area (Lightfoot and Bond 2013) and there are recognised barriers to the successful inclusion of pupils with DS, including negative attitudes from both peers and teaching staff (Fox et al 2004). Research (Boys 2003: Lyons et al 2016 identifies the lack of support from educational staff for children with DS as being the result of insufficient knowledge around the needs of individuals and limited professional development opportunities regarding inclusive practice (Mulholland and O'Connor 2016). Furthermore, Hodkinson (2010) opines that there is a link between inclusion and academic accountability, suggesting that league tables and examination results can lead to a reluctance to include individuals with learning disabilities in mainstream settings.…”
Section: Introductionmentioning
confidence: 99%